2012 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--22208
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing a Collaborative Virtual Reality Environment as a Training Tool for Construction Students

Abstract: Tulio Sulbaran received his Ph.D. in civil engineering from Georgia Institute of Technology with a concentration in construction management and with a minor in computer engineering and strong statistical background. He has more than eight years of work experience in the A/E/C (architecture, engineering, and construction) industry with office and field experience in scheduling, estimating, and project management in the United States and several international locations, including Venezuela, Singapore, Brunei, Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Girvan argues that some use terms synonymously with VR and/or VEs, while others use these same terms to classify different types of VEs, thus creating a fragmented understanding of what these are (and what they are not). Girvan's point is reflected in the reviewed literature of this paper: while some studies identify Second Life as a "virtual environment" or "virtual world" (e.g., Terzidou et al, 2012), others refer to it as "virtual reality" (e.g., Sulbaran and Jones, 2012). To prevent further confusion with technologies with similar technical features, Girvan suggests to conceptualize VEs as 'shared, simulated spaces which are inhabited and shaped by their inhabitants, who are represented as avatars [that] mediate our experience of this space as (.…”
Section: Systems Developed And/or Established For Vrclmentioning
confidence: 92%
“…Girvan argues that some use terms synonymously with VR and/or VEs, while others use these same terms to classify different types of VEs, thus creating a fragmented understanding of what these are (and what they are not). Girvan's point is reflected in the reviewed literature of this paper: while some studies identify Second Life as a "virtual environment" or "virtual world" (e.g., Terzidou et al, 2012), others refer to it as "virtual reality" (e.g., Sulbaran and Jones, 2012). To prevent further confusion with technologies with similar technical features, Girvan suggests to conceptualize VEs as 'shared, simulated spaces which are inhabited and shaped by their inhabitants, who are represented as avatars [that] mediate our experience of this space as (.…”
Section: Systems Developed And/or Established For Vrclmentioning
confidence: 92%
“…The first was by Maratou et al (2016), who tested the use of a virtual world role-playing game to teach PM software and confirmed its positive effect on learning. The use of VR for construction management students was discussed by Sulbaran & Jones (2012), who found that students do not gain real-world experience during their studies and, therefore, end up unprepared for realistic situations. The study aimed to use VR to simulate a construction project with game elements for teaching purposes.…”
Section: Category Authorsmentioning
confidence: 99%
“…Most of the implementation papers (i.e., 19) focus on the impact of VR on learning. In some cases, this interest is made explicit in the goal to analyze the impact of VR in spatial visualisation (Ceylan, 2020;Bartosh and Anzalone, 2019), tacit knowledge acquisition (Wu et al, 2019a), knowledge transfer, knowledge retention (Eiris et al, 2021;Beh et al, 2021) as well as in allowing students to live a realistic experience (Sulbaran and Jones, 2012).…”
Section: Fig 4: Types Of Papers (Left) and Their Distribution Per Yea...mentioning
confidence: 99%
“…Between 2011 and 2015, some courses also adopted virtual worlds such as Second Life (e.g., Ku and Mahabaleshwarkar, 2011) to simulate, through an avatar, an experience in the construction sector. Study by Sulbaran and Jones (2012), for example, adopted Second Life as a virtual platform to create a socially interactive role-play experience for students to learn about construction site safety, construction sequences and resource management. Recently, since 2019, content such as 360-degree images or time lapse videos have been used to reconstruct and allow students to visit a construction site, albeit in a virtual environment.…”
Section: Fig 12: Vr Configurations Used In Construction Education Bas...mentioning
confidence: 99%